2017
DOI: 10.1063/1.4979475
|View full text |Cite
|
Sign up to set email alerts
|

Giant field-induced adiabatic temperature changes in In-based off-stoichiometric Heusler alloys

Abstract: Direct measurements of the adiabatic temperature change (ΔTAD) of Ni50Mn35In14.5B0.5 have been done using an adiabatic magnetocalorimeter in a temperature range of 250–350 K, and with magnetic field changes up to ΔH = 1.8 T. The initial susceptibility in the low magnetic field region drastically increases with temperature starting at about 300 K. Magnetocaloric effects parameters, adiabatic temperature changes, and magnetic entropy changes were found to be a linear function of H2/3 in the vicinity of the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Known materials made of abundant and non-toxic elements include those with body-centered cubic (bcc) A2, B2 [30], or Heusler structures [80,[92][93][94][95][96][97][98][99][100][101][102][103] (with or without a possible tetragonal distortion), Mn 0.5 Fe 0.5 NiSi 1−x Al x [31] with TiNiSi-type orthorhombic to Ni 2 In-type hexagonal phase transition, LaFe 13−x Si x [87,104,105] with the NaZn 13 -type 1:13 phase (Figure 3), a subset of magnetic shape memory alloys (SMA) containing Ni and Mn, manganites based on La 0.7 Ca 0.3 MnO 3 , etc.…”
Section: ∆S T T C (K) ∆T S (K)mentioning
confidence: 99%
“…Known materials made of abundant and non-toxic elements include those with body-centered cubic (bcc) A2, B2 [30], or Heusler structures [80,[92][93][94][95][96][97][98][99][100][101][102][103] (with or without a possible tetragonal distortion), Mn 0.5 Fe 0.5 NiSi 1−x Al x [31] with TiNiSi-type orthorhombic to Ni 2 In-type hexagonal phase transition, LaFe 13−x Si x [87,104,105] with the NaZn 13 -type 1:13 phase (Figure 3), a subset of magnetic shape memory alloys (SMA) containing Ni and Mn, manganites based on La 0.7 Ca 0.3 MnO 3 , etc.…”
Section: ∆S T T C (K) ∆T S (K)mentioning
confidence: 99%
“…12,15,19 In recent studies, we have reported on the magnetostructural, magnetic, magnetocaloric, and magnetoresistance properties of bulk Ni-Mn-In-B based systems. [20][21][22] …”
Section: Introductionmentioning
confidence: 99%
“…These types of transitions are commonly observed in alloys containing lanthanide elements (rare earths), due to their electronic configuration [13,14]. Alloys based on these elements have the best magnetocaloric response; however, these materials are very expensive, due to their obtaining and processing methods.The use of 3d transition elements has also attracted considerable attention, due to their unique physical properties and promising applications, such as magnetic field-induced shape memory effect, magnetic field-induced strain, magnetocaloric effect, and magnetoresistance [15][16][17][18]. The magnetocaloric effect in Ni-Mn and Ni-Mn-Z (Z = Ni, Cu, Co, Fe, Mn, and Cr) Heusler alloys leads to an existing field, which is considerably less expensive and higher effective than conventional rare-earth-based magnetocaloric alloys [15].…”
mentioning
confidence: 99%
“…The magnetocaloric effect in Ni-Mn and Ni-Mn-Z (Z = Ni, Cu, Co, Fe, Mn, and Cr) Heusler alloys leads to an existing field, which is considerably less expensive and higher effective than conventional rare-earth-based magnetocaloric alloys [15]. It has been found that the magnetic properties and phase stability of these systems are sensitive to small changes in the concentrations of the parent components and the substitution of Ni, Mn, or In by an additional element Z [15][16][17][18]. The phenomena related to the magneto-structural transitions are highly dependent on the weighted average radius of the constituent ions [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation